2014
DOI: 10.1088/0031-9155/59/21/6431
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gold nanoparticle radiosensitization mechanisms using a free radical scavenger and protons of different energies

Abstract: Gold nanoparticles (GNPs) have been shown to sensitise cancer cells to X-ray radiation, particularly at kV energies where photoelectric interactions dominate and the high atomic number of gold makes a large difference to X-ray absorption. Protons have a high cross-section for gold at a large range of relevant clinical energies, and so potentially could be used with GNPs for increased therapeutic effect.Here, we investigate the contribution of secondary electron emission to cancer cell radiosensitisation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 36 publications
(55 reference statements)
1
58
0
Order By: Relevance
“…19 Jeynes et al used a low-energy proton beam to irradiate bladder carcinoma cells loaded with 50 nm Au-NPs, but no enhancement of cell killing was observed. 20 In contrast, our recent study using lung cancer cells showed sensitization when 25 keV/lm protons were used, but not with 10 keV/lm protons in combination with 10 nm Au-NPs. 21 Additionally, exposure to heavier ions seems to provide a marked sensitization effect.…”
Section: Introductionmentioning
confidence: 69%
“…19 Jeynes et al used a low-energy proton beam to irradiate bladder carcinoma cells loaded with 50 nm Au-NPs, but no enhancement of cell killing was observed. 20 In contrast, our recent study using lung cancer cells showed sensitization when 25 keV/lm protons were used, but not with 10 keV/lm protons in combination with 10 nm Au-NPs. 21 Additionally, exposure to heavier ions seems to provide a marked sensitization effect.…”
Section: Introductionmentioning
confidence: 69%
“…They found an ER of 1.22-1.43 at 2 Gy for the 1.3 MeV beam depending on the GNP size, but no significant enhancement for the 4 MeV beam. Similarly, Jeynes et al 17 did not see any radiosensitization effect when RT-112 bladder cancer cells were irradiated with 3 MeV protons, although their result may be an outcome of the relatively low GNP concentration used. In spite of the experimental validation of GNP enhanced proton therapy, computational models have suggested a much lower radiosensitization effect.…”
Section: Introductionmentioning
confidence: 90%
“…No clear effect has been seen with protons of 3 MeV and 6 or 50 nm gold NP (Jeynes et al, 2014;Liu et al, 2010) though others publications evoke the beneficial proton-NP combination. For iron NP, Kim obtained a 20-28% increase of cell death with 14 nm FeNP and 45 MeV proton but also with 2 nm and 13 nm gold NP (Kim et al, 2010).…”
Section: Is There An Energy Dependency?mentioning
confidence: 96%